Analysis of Early Childhood Education Teacher Training Needs in the Utilisation of Artificial Intelligence-Based Applications - Lusiana Wulansari; Mulyadi Mulyadi; Siti Suedah; Zita Bintang Maharani; Hanna Hottenrott (Ceddi Journal of Education, 2025)
Educational transformation in the Society 5.0 era positions artificial intelligence (AI) as a strategic technology with the potential to improve the quality of learning, including in early childhood education (PAUD). However, the implementation of AI in PAUD units remains suboptimal due to limited teacher competence, attitudes towards technology, and institutional support. This study aims to analyse the training needs of PAUD teachers in the use of AI-based applications by examining the influence of teachers' digital competence, openness to technology, access to infrastructure, and institutional support on these needs. The study used a quantitative explanatory approach with purposive sampling to examine 150 non-formal PAUD teachers in the Arcamanik District, Bandung City. Data were collected using a standardised questionnaire that had been tested for validity and reliability, and were then analysed using multiple linear regression. The results showed that all four variables simultaneously had a significant effect on PAUD teacher training needs, with an Adjusted R² value of 0.659. In part, openness towards technology and teachers' digital competence were the most dominant predictors. These findings emphasise the importance of designing PAUD teacher training programs that are comprehensive, sustainable, and aligned with institutional policies that are adaptive to the development of AI-based technologies.